PERBANDINGAN PENGGUNAAN LKS (PREDICT-OBSERVE-EXPLAIN) DENGAN LKS KONVENSIONAL TERHADAP HASIL BELAJAR - Dewi Nurhidayati; Feriansyah Sesunan; Ismu Wahyudi (Jurnal Pembelajaran Fisika, 2017)
This research aims to determine differences in learning outcomes betweenusing POE student worksheet with conventional student worksheet in Static Fluid topic. This research uses a non-equivalent control group design. Data were tested with Grouping Learning Outcome Technique, N-gains Analysis, normality test, homogeneity test, and independent T-test. Based on the resultof hypothesis test,it has known that there are differences in learning outcomesbetween using the POE student worksheet and conventional student worksheeton cognitive and psychomotor. Cognitive and psychomotor learning outcomes by using POE student worksheets is higher than cognitive and psychomotor learning outcomes by using conventional student worksheet.The average value of N-gain is 0.83, whereas psychomotor learning outcomes percentage in the experiment class 33 students (100%) of students who reach psychomotorpassi.Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar antara menggunakan LKS POE dengan LKS konvensional pada materi Fluida Statis. Desain penelitian ini menggunakan bentuk non-equivalent control grup design. Data diuji dengan Teknik Pengelompokan Hasil Belajar, Analisis N-gain, Uji Normalitas, Homogenitas, dan Uji Inde-pendent T-test. Berdasarkan hasil uji hipotesis, diketahui bahwa terdapat perbedaan hasil belajar menggunakan LKS berbasis POE dengan LKS konvesional pada ranah kognitif dan psikomotor hasil belajar ini menggunakan LKS berbasis POE lebih tinggi dibandingkan LKS konvensional pada ranah kognitif didapat nilai rata-rata N-gain sebesar 0,839, sedangkan hasil belajar ranah psikomotor pada kelas ekperimen sebanyak 33 siswa (100%) siswa yang mencapai KKM psi-komotorik.Kata Kunci: Fluida Statis, Konvensional, LKS POE.